Targeting signaling factors for degradation, an emerging mechanism for TRAF functions - Yang, Xiao-Dong; Sun, Shao-Cong (Immunological reviews, 2015)
Summary Tumor necrosis factor receptor (TNFR)‐associated factors (TRAFs) form a family of proteins that are best known as signaling adapters of TNFRs. However, emerging evidence suggests that TRAF proteins, particularly TRAF2 and TRAF3, also regulate signal transduction by controlling the fate of intracellular signaling factors. A well‐recognized function of TRAF2 and TRAF3 in this aspect is to mediate ubiquitin‐dependent degradation of nuclear factor‐κB (NF‐κB)‐inducing kinase (NIK), an action required for the control of NIK‐regulated non‐canonical NF‐κB signaling pathway. TRAF2 and TRAF3 form a complex with the E3 ubiquitin ligase cIAP (cIAP1 or cIAP2), in which TRAF3 serves as the NIK‐binding adapter. Recent evidence suggests that the cIAP‐TRAF2‐TRAF3 E3 complex also targets additional signaling factors for ubiquitin‐dependent degradation, thereby regulating important aspects of immune and inflammatory responses. This review provides both historical aspects and new insights into the signaling functions of this ubiquitination system.